Concept and functions of building a private network (VPN) (MCIT: Proceedings of International scientific and practical conference, 2021)
As companies and organizations began to actively use computers in various areas of their work,  these computers needed to be integrated into a common network for fast data transfer and efficient interaction. However, this connection must have been reliable and secure.
Keywords: Virtual Private Network, network services, local area networks